Interfacial p–n coupling in Cu3N/1T-MoS2 heterojunctions drives efficient and durable acidic hydrogen evolution - Huang, Tianjiao; Xia, Wu; Joshua, Fnu; Ponnusamy, Vaishnavii Subbiah; Zhang, Qipeng; Kumar, Sachin; Yu, Ao (Frontiers in Energy Research, 2025)
Rational interfacial engineering is crucial to designing non-precious electrocatalysts for the hydrogen evolution reaction (HER). Here we report a Cu3N/1T-MoS2 heterojunction in which ultrathin 1T-MoS2 nanosheets are conformally grown on conductive p-type Cu3N nanocubes. Spectroscopy and microscopy reveal intimate lattice contact and interfacial strain, while XPS indicates charge redistribution across the junction. In 0.5 M H2SO4, the optimized 1:1 composite delivers an overpotential of 387 mV at 50 mA cm−2 and a Tafel slope of 57 mV dec−1, outperforming both constituents (MoS2 ≈ 456 mV; Cu3N inactive at this current density). Continuous operation for 150 h demonstrates excellent acid stability. Electrochemical impedance and double-layer capacitance analyses show the lowest charge-transfer resistance and the highest electrochemically active surface area among all samples (Cdl = 103.6 mF cm−2), corroborating rapid electron transport and abundant accessible sites. The activity enhancement arises from a p–n heterojunction with a built-in field that promotes directional electron flow to MoS2 active edges, together with strain-induced defect exposure. This work identifies Cu3N as an effective platform to stabilize conductive MoS2 and provides design rules for interface-engineered HER catalysts.